Identity-based anonymous cloud auditing scheme with compact tags - Chenxin LU; Bing CHEN; Ning DING; Liquan CHEN; Ge WU (网络与信息安全学报)
Cloud storage has the advantages of high efficiency and scalability.Users can save local storage cost and share data with others through cloud storage technology.However, when data is uploaded to cloud servers, its owner also loses the physical control, and hence there needs a corresponding mechanism to ensure the integrity of data stored in the cloud.The Provable Data Possession (PDP) mechanism allows users or a Third-Party Auditor (TPA) appointed by the user to verify data integrity.In practice, data is usually maintained by multiple users.Users may reveal their identities while making an integrity verification request in traditional auditing processes.Anonymous cloud auditing ensures anonymity of users against the TPA during auditing.Currently, in identity-based systems, anonymous cloud auditing schemes usually resort to identity-based ring signature or group signature schemes.As a result, the size of a tag is related to the number of users, which makes it not compact and causes high storage cost.In order to solve this issue, a general construction of identity-based anonymous cloud auditing scheme was proposed.With a signature scheme and an anonymous cloud auditing scheme, a concrete identity-based anonymous cloud auditing scheme based on the general construction was proposed.It combined theBLS signature and an anonymous cloud auditing scheme with compact tags.The main advantage of this solution is that the tags are compact, which can significantly reduce storage cost and improve storage efficiency.Furthermore, the uncheatability and anonymity of the scheme are proved.